2015
DOI: 10.1186/s40064-015-1035-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and outcome features of superficial high-grade and deep low-grade squamous cell carcinomas of the penis

Abstract: PurposeTo report the clinicopathologic and outcome features of superficial high-grade and deep low-grade penile squamous cell carcinomas.MethodsFrom a retrospectively-collected series of patients with penile cancer we identified 41 cases corresponding to 12 superficial high-grade tumors and 29 deep low-grade tumors. As outcomes we evaluated inguinal lymph node status, presence of tumor relapse, final nodal status, and cancer-specific death. Follow-up ranged from 0.8 to 386.7 months (mean 152.5 months, median 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Even less frequent are grade III tumors invading only LP. 22 In a large study, we found only 2 cases of superficial grade III carcinomas among 333 consecutive cases. 13 It is posible that in future models LVI, PNI and grade would be inserted for substratification of stages pT2 and pT3.…”
Section: Special Considerations On the Heterogeneity Of Verrucous Car...mentioning
confidence: 92%
See 1 more Smart Citation
“…Even less frequent are grade III tumors invading only LP. 22 In a large study, we found only 2 cases of superficial grade III carcinomas among 333 consecutive cases. 13 It is posible that in future models LVI, PNI and grade would be inserted for substratification of stages pT2 and pT3.…”
Section: Special Considerations On the Heterogeneity Of Verrucous Car...mentioning
confidence: 92%
“…According to this view, there are no metastases in grade 1 tumors, disregarding their invasion depth and there is a high incidence of metastasis in grade 3 tumors. 15,22 The separation of stages T2 and T3 according to tumor invasion of CS or CC need to be reevaluated. In our experience, tumor invading superficial CS, that is, no more than 5 mm in depth, and low-grade (grade 1 or 2) behaves as those invading LP, with minimal rate of nodal metastasis.…”
Section: Future Issuesmentioning
confidence: 99%
“…In these cases the diagnosis of "verruciform tumor, not otherwise specified" may be appropriate. Histological grading is particularly useful in these situations since it seems that it has a greater impact on prognosis than tumor depth or thickness [13].…”
Section: Differential Diagnosis Of Verruciform Tumorsmentioning
confidence: 99%
“…Histologic grade has been repeatedly reported as an important prognostic factor [4,15]. High grade tumors tend to metastasize and disseminate much more frequently than low-grade tumors, even if superficially located [13]. For consistency we propose the use of a simple 3-tier system which emphasizes both ends of the spectrum [15]:…”
Section: Histological Gradementioning
confidence: 99%
See 1 more Smart Citation